oh sport - Grigoryeva, Elena (project baikal, 2017)
In 1912, art competitions were held as a part of the Olympic Games for the first time. The gold medal for literature was awarded to Pierre de Coubertin for his “Ode to Sport”. The words “Oh sport, you are the peace” from the final part of the Ode became winged and were translated into a number of languages. But the play of meanings “peace” and “world” can be observed only in the Russian word “mir”.Pierre de Coubertin’s original words are: “O Sport, tu es la Paix!”. It means that sport is opposite to war. A lot of things have changed since then in the world of sports. Strong emotional reactions, severe struggles for victory, and, above all, the money flows comparable to federal expenditures on armaments make top-class sports akin to local wars, rather than to peaceful athletic contests.The shift of sports from arts to a powerful industry has had a big impact on architecture of sports venues within the last 50 years. We present a collection of stadiums for the 2018 World Football Championship, as well as sports venues in Irkutsk, Tomsk and Krasnodar. Krasnoyask architects tell us about preparations for the Universiade 2019.Top-class sports have been professionalized. And what about mass sports? As the popular free-for-all rinks and courts disappear, where do mass sports go? Architects and urban planners not only search for the sites to allocate mass sports in the cities, they also go in for sports. Architects-mountain skiers from Siberia and Ural have gathered at their Forum. ARCHIGESH in Mountain Shoria becomes international.Sports play a very important and diverse role in the present-day global culture. On the occasion of the 105th anniversary of Coubertin’s Ode we would like to wish sports to return to the main words of the Ode and to correspond with them: “Oh sport, you are the peace”.
Keywords: sports; competitions; sports venues; architecture